Mengevaluasi Level Pemahaman Konsep Hidrolisis Garam Peserta Didik Menggunakan Tes Diagnostik Pilihan Ganda Empat Tingkat - Ivani Kusnadi Suteno; Lukman Abdul Rauf Laliyo*; Hendri Iyabu; Romario Abdullah (Jurnal Pendidikan Sains Indonesia, 2021)
The ability of students to understand and use concepts is the main key in scientifically explaining various chemical phenomena in nature. This ability develops relatively, often with the development of the learner level. This study aims to understand the level of understanding of the concept of salt hydrolysis of class XI high school students and chemistry students in the I, II, III and IV years and non-chemistry students with a total sample of 875 respondents. The instrument used in this study was a four-level multiple choice test. This diagnostic test combines the measurement of knowledge and reasoning with the level of self-confidence, as a reflection of the level of mastery of concepts. The data analysis technique used is quantitative, using SPSS 25 software, namely the non-parametric test (Kruskal Wallis test), comparing the significance value (Asmp. Sig) with a probability of 0.005. The results showed that the significance value of 0.00 was less than 0.05; That is, there is a significant difference in the level of understanding of the salt hydrolysis concept of students. The level of understanding of the concept of high school students is better than the first, second, third, and fourth year students in chemistry and non-chemistry students. These findings reinforce the story that although students have experienced learning experiences at a higher level, it does not guarantee the development of mastery of understanding the concept of hydrolysis